Analisis Penyebaran Aspal Buton Berdasarkan Data Bor Di Daerah Lawele - Suharni Suharni; Asrim Asrim; Sarman Sarman (Universitas Muslim Indonesia, 2022)
Buton asphalt is a natural asphalt on Buton Island, Southeast Sulawesi. To meet the target of Buton asphalt production, it is necessary to develop an area in the Lawele area as one of the asphalt producing areas on Buton Island. The purpose of this study was to determine the distribution of Buton asphalt and the form of asphalt deposits in the Lawele area, Buton Regency. The research methodology is divided into literature study, data collection, data processing, analysis and discussion and conclusions. The data used in this research is drill data which includes coordinates, elevation, lithology type, thickness, and depth of drill point. Data processing and analysis in this study was carried out through lithological correlation using RockWorks 17 software. Lithological correlation was carried out to determine the continuity of the asphalt layer from one drill point to another drill point. Based on the results of the analysis on the cross-sectional correlation that has been carried out, it can be concluded that the direction of distribution of asphalt deposits in the research area in line 1 and line 3 is from west to east with a tabular morphology of asphalt deposits, while on line 2 is single deposit and asphalt seepage is found.